2020
DOI: 10.1021/acsenergylett.0c02205
|View full text |Cite
|
Sign up to set email alerts
|

Redox Flow Battery Membranes: Improving Battery Performance by Leveraging Structure–Property Relationships

Abstract: Membranes are a critical component of redox flow batteries (RFBs), and their major purpose is to keep the redox-active species in the two half cells separate and allow the passage of chargebalancing ions. Despite significant performance enhancements in RFB membranes, further developments are still needed that holistically consider conductivity, selectivity, stability, sustainability, and cost. In this Focus Review, structure−property relationships that have led to advances in membranes for various RFB types (v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 90 publications
(394 reference statements)
0
67
0
Order By: Relevance
“…Furthermore, it can be assumed that the adoption of SPEEK can reduce the cost of the membrane from 39 % of the entire ICRFB system to 5 %. [70] Hence, the total manufactur-ing cost of the ICRFB system is postulated to be reduced from 194 to $124 kWh À 1 . In a separate case, the estimated production cost of SPEEK membrane can be as low as $40 m À 2 , which is around 10 times lower than the price of Nafion membranes.…”
Section: Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it can be assumed that the adoption of SPEEK can reduce the cost of the membrane from 39 % of the entire ICRFB system to 5 %. [70] Hence, the total manufactur-ing cost of the ICRFB system is postulated to be reduced from 194 to $124 kWh À 1 . In a separate case, the estimated production cost of SPEEK membrane can be as low as $40 m À 2 , which is around 10 times lower than the price of Nafion membranes.…”
Section: Membranesmentioning
confidence: 99%
“…After comparing the performance of the SPEEK membrane with that of N115, they concluded that such an attempt to reduce membrane cost can be achieved (see Figure 9c,d). Furthermore, it can be assumed that the adoption of SPEEK can reduce the cost of the membrane from 39 % of the entire ICRFB system to 5 % [70] . Hence, the total manufacturing cost of the ICRFB system is postulated to be reduced from 194 to $124 kWh −1 .…”
Section: Research Status Of Key Components In Icrfbmentioning
confidence: 99%
“…In addition to AEMFCs, AEMs also can be used in other batteries, such as Zn-metal alkaline batteries 100 and redox flow batteries. 101 Zn-metal alkaline batteries have been developed for a long time, however, it is still nonchargeable because of uncontrollable side reactions and irreversible anode reaction. Tang has proposed a cobaltocenium-containing polyelectrolyte for rechargeable Zn-metal alkaline batteries with excellent ionic conductivity and stability.…”
Section: Other Battery Categoriesmentioning
confidence: 99%
“…In order to minimize the electrochemical polarization and capacity fade, and maximize the power density, energy density, lifetime and efficiency, membranes are expected to allow supporting ion conduction while blocking the crossover of redox-active species. 10–15 Conventional membranes, represented by perfluorosulfonic acid membrane (Nafion, ∼$500 per m 2 ) with a dense and nanophase-separated structure, have been widely employed in the realm of electrochemical energy storage during the past decades owing to excellent stability and high ion conductivity. 16–19 However, the high cost and low selectivity hinder their widespread applications in RFBs.…”
Section: Introductionmentioning
confidence: 99%